Identifcation of genotypescarriers of resistance to tan spot Ptr ToxA and Ptr ToxB of Pyrenophora tritici-repentis in common wheat collection - A. М. Kokhmetova; Sh. Ali; Z. Sapakhova; M. N. Atishova (Вавиловский журнал генетики и селекции)
Pyrenophora tritici-repentis (Ptr) is the causative agent of tan spot, one of the yield limiting diseases of wheat, rapidly increasing in wheat growing countries including Kazakhstan. The aim of this study was the identifcation of wheat genotypes with resistance to Ptr race 1 and race 5 and their hostselective eﬀectors (toxins) Ptr ToxA and Ptr ToxB. A common wheat collection of 41 accessions (38 experimental and 3 controls) was characterized using the molecular markers Xfcp623 and XBE444541, diagnostic for the Tsn1 and Tsc2 genes conferring sensitivity to fungal toxins. The coincidence of the marker XBE444541 with resistance to race 5 was 92.11 %, and with Ptr ToxB, 97.37 %. Genotyping results using the marker Xfcp623 confrmed the expected response to Ptr ToxA; the presence/absence of the marker Xfcp623 completely (100 %) coincided with sensitivity/resistance to race 1 and Ptr ToxA. This demonstrates the reliability of the diagnostic marker Xfcp623 for identifying wheat genotypes with resistance to the fungus and insensitivity to Ptr ToxA. The study of the reaction of wheat germplasm to the fungal inoculation and toxin infltration showed that out of 38 genotypes analyzed 30 (78 %) exhibited resistance to both race 1 and race 5, and insensitivity to toxins Ptr ToxA and ToxB. Of most signifcant interest are eight wheat genotypes that showed resistance/insensitivity both to the two races and two toxins. The results of phenotyping were reconfrmed by the molecular markers used in this study. Sensitivity to Ptr ToxB is not always correlated with susceptibility to race 5 and is dependent on the host’s genetic background of the wheat genotype, i. e. on a specifc wheat genotype. The results of the study are of interest for increasing the efciency of breeding based on the elimination of the genotypes with the dominant alleles Tsn1 and Tsc2 sensitive to the toxins Ptr ToxA and ToxB. The genotypes identifed will be used in wheat breeding for resistance to tan spot.